Attitude toward Poverty among Academicians: Social Care Institution Workers and General Population in Kuala-Lumpur, Malaysia. Proceedings of the 4th ASEAN Conference on Psychology, Counselling, and Humanities (ACPCH 2018) (2019)
The aim of the present study is to investigate the differences in attitude among three groups of people as academicians, social institution workers and general population that explain about poverty. A total of 105 respondents were recruited in Kuala-Lumpur. Attitude toward Poverty Short Form Scale was used to determine the attitude toward poverty. There are 3 constructs in this scale as personal deficiency, stigma and structural perspectives. The participants were requested to complete the Attitude toward Poverty Short Form Scale. Statistical result of One-way ANOVA test revealed that academicians and general population ascribed personal deficiency more than stigma and structural perspectives to explain poverty. Social care institution workers perceived personal deficiency as least important determinant to poverty. Demographic profiles such as gender, higher education status and high income individuals emphasized more on individualistic perspective too. The results provide evidence that poverty is ascribed to individual insufficient effort. This indicates that appropriate approach can be implemented to modify behavior of these individuals.